Mathematical model and analysis of the effect of awareness program on diabetes dynamic - Farhah Ramli; Auni Aslah Mat Daud (Penerbit Universiti Kebangsaan Malaysia, 2025)
The prevalence of diabetes worldwide is increasingly concerning, affecting individuals of all ages due to genetic predisposition and environmental factors. Diabetes can be prevented or delayed through lifestyle interventions such as a balanced diet, regular physical activity, and weight management. However, a lack of awareness often leads to late diagnosis and progression to diabetes, increasing the burden on the healthcare system. Public awareness plays a crucial role in promoting early interventions and encouraging individuals to adopt healthier behaviours. Considering the benefits of awareness, this study explores its impact on the development of diabetes through a nonlinear mathematical model. This model consists of six subpopulations representing different health statuses and the cumulative of media-driven awareness campaigns. We developed a flow diagram and made several assumptions to describe population dynamics, which led to a system of nonlinear ordinary differential equations. Local stability is analysed using the Jacobian matrix and the Lienard-Chipart criterion, while global stability is examined through the Lyapunov function. Numerical simulations of the model are carried out to verify and illustrate the analytical results. The results indicate that controlling the growth of media-driven awareness programs, increasing the transition of unaware healthy individuals gaining awareness or increasing the transition of unaware prediabetes individuals gaining awareness can reduce the burden of diabetes. Furthermore, exposure to media-driven awareness campaigns targeting unaware individuals may help in reducing the progression of prediabetes and diabetes when they begin adopting a healthy lifestyle.